Eksperimentasi Pembelajaran Matematika dengan Model PBL Berbasis Think Pair Share dan Missouri Mathematic Project Ditinjau dari Kemampuan Komunikasi Matematis - Sari, Yuli Ambar; , Dra. Nining Setyaningsih, M.Si; , Sri Rejeki, M.Pd, M.Sc (2015)
This study aims to analize and examine: 1) the different on PBL based Think Pair Share and Missouri Mathematic Project Models on students' mathematics achievement, 2) the diferent on the level of students' mathematics communication skills on students mathematics achievement, 3) the effect of interaction between learning models and the level srudents' mathematical communication skill on students mathematics achievement. The population of this study is grade XI students at SMK Negeri 9 Surakarta 2014/2015. Two classes were chosen as the sample of this study by cluster random sampling, and it is obtained grade XI TKJ A as Eksperiment class and XI DKV as Control class. The data collection was conducted by questionnaires,test,and documentation. The data were analyzed using different number of cell analysis of variance with α = 5%. Previously,the normality test with Lilliefors method and analysis homogeneity test with Bartlett method were conducted of the prerequisite analysis. Based on the analysis, it can be concluded that: 1) there is effect of PBL based Think Pair Share and Missouri Mathematic Project models on students mathematics achievement,2) there is effect the level of students' mathematics communication skills on students mathematics achievement,3) there is no interaction between learning models and the level students' mathematical communication skill on students mathematics achievement.